Inflammation and reactive oxygen species as disease modifiers in epilepsy. (1st May 2020) - Terrone, Gaetano; Balosso, Silvia; Pauletti, Alberto; Ravizza, Teresa; Vezzani, Annamaria
Abstract: Neuroinflammation and reactive oxygen and nitrogen species are rapidly induced in the brain after acute cerebral injuries that are associated with an enhanced risk for epilepsy in humans and related animal models. These phenomena reinforce each others and persist during epileptogenesis as well as during chronic spontaneous seizures. Anti-inflammatory and anti-oxidant drugs transiently administered either before, or shortly after the clinical onset of symptomatic epilepsy, similarly block the progression of spontaneous seizures, and may delay their onset. Moreover, neuroprotection and rescue of cognitive deficits are also observed in the treated animals. Therefore, although these treatments do not prevent epilepsy development, they offer clinically relevant disease-modification effects. These therapeutic effects are mediated by targeting molecular signaling pathways such as the IL-1β−IL-1 receptor type 1 and TLR4, P2X7 receptors, the transcriptional anti-oxidant factor Nrf2, while the therapeutic impact of COX-2 inhibition for reducing spontaneous seizures remains controversial. Some anti-inflammatory and anti-oxidant drugs that are endowed of disease modification effects in preclinical models are already in medical use and have a safety profile, therefore, they provide potential re-purposed treatments for improving the disease course and for reducing seizure burden. Markers of neuroinflammation and oxidative stress can be measured in blood or by neuroimaging, therefore they represent testable prognostic and predictive biomarkers for selecting the patient's population at high risk for developing epilepsy therefore eligible for novel treatments. This article is part of the special issue entitled 'New Epilepsy Therapies for the 21st Century – From Antiseizure Drugs to Prevention, Modification and Cure of Epilepsy'. Highlights: Neuroinflammation and oxidative stress act as disease modifiers in acquired epilepsies. Antiinflammatory and antioxidant drugs administered during epileptogenesis reduce seizure burden in rodents. These treatments offer neuroprotection and improve cognitive deficits. Neuroinflammation and oxidative stress may generate biomarkers for epilepsy. Clinical studies showed that specific antiinflammatory drugs reduce pharmacoresistant seizures.